Effects of N-Doped Titanium Oxide on Photocatalytic Properties - Li, X.; Liu, Y.Y. (Asian Journal of Chemistry, 2012)
In this work, N-doped TiO2 powders were prepared by sol-gel procedure using NH4NO3 as the nitrogen source. The photocatalytic activity was evaluated by measuring the decomposition of methyl orange under UV irradiation. X-ray diffractometry and field emission scanning electron microscopy were applied to characterize crystal structure and morphology. The mixtures of rutile and anatase phase co-exist in the resulted N-doped TiO2 powders. Amounts of nitrogen doping in TiO2 can effectively improved the photocatalytic activity of TiO2. The change of phase composition that derived from the different content of nitrogen doping also has influence on photocatalytic activity. Photodegradation of methyl orange in 1 h was about 63 % and the crystallite size was about 60 nm.